Analisis Tugas Rutin Penata Usaha Pimpinan Dalam Memperlancar Tugas Pimpinan Fakultas Ekonomika Dan Bisnis - Claudia Kintani Audi; Ismiyati Ismiyati; Dhela Septian Anggaretta (Jurnal Sekretaris dan Administrasi Bisnis, 2025)
Routine tasks are tasks or jobs that must be performed regularly and consistently in a similar pattern. Routine tasks include activities that are repetitive and part of established work procedures. This study aims to analyze the routine tasks of the Chief Business Administrator in facilitating the duties of the Chairperson of the Faculty of Economics and Business, State University of Semarang. The research method used is a qualitative approach with a case study research strategy. The data collection techniques used were interviews, observation and documentation.The results showed that the routine tasks of the Chief Business Administrator as a whole had been carried out well and helped expedite the duties of the Chief. However, there are several things that need to be improved by the Chief Business Administrator, namely speed in making letters, time management, accuracy of letter distribution, speed of service and Microsoft Office competence.The conclusion of this study is that the implementation of routine tasks of the Chief Business Administrator as a whole has helped expedite the duties of the Chairman in correspondence, administration, archiving, preparation of the Chairman's activity schedule, serving guests of the Chairman, providing information needed by the Chairman, carrying out other official duties and can save time and focus of the Chairman.